INVESTIGATION INTO THE FACTORS THAT REDUCE THE ENGLISH LEARNING PERFORMANCE STUDENTS OF SMKN 3 TANA TORAJA - Sambe, Lince; Tanan, Yuliana; Sau'Langi, Thomas; Marusa, Arnold (La Ogi : English Language Journal, 2024)
This study is a qualitative descriptive study study. This study investigated factors causing the low learning results of Students of SMKN 3 Tana Toraja, in English Class. This study can be the reference for English lecturers in determining the best strategy in teaching English to Automotive Engineering students. The respondents were the students who got bad scores in English class. To find out the internal and external factors causing the low learning results of the students, they were given a questionnaire. The results show that the intelligence factor, the difficulty of getting friends to practice English, the explanation of theEnglish lecturer, and the laziness to study can be some factors causing the low learning result of some SMKN 3 Tana Toraja students in English class. Meanwhile, the internal and the external factors like physical health, attention, interest, motivation to learn English, teaching methods, lessons, the relationship with the lecturer, learning tools, classroom condition, the respondents' learning methods both in class and outside class are not the cause of the low learning results of the respondents in English class.